ANALISIS PERBEDAAN KINERJA KARYAWAN PADA LINE OPP PT. SIMATELEX MANUFACTORY DENGAN KINERJA KARYAWAN PT. KARYASINDO SAMUDRA BIRU SHIPYARD - M. Arpah; Mohamad Aras; Hendri Kremer; Daris Purba; Hazriyanto Hazriyanto (JURNAL CAFETARIA, 2023)
This study studied the differences in employee performance in two manufacturing companies in Batam: Line OPP PT Simatelex Manufactory and PT Karyasindo Samudra Biru Shipyard. Both companies have problems with employee performance, that is, employees cannot achieve the specified targets. This study is hypothetical research. The hypothesis in this study is that there are differences in employee performance on the OPP Line of PT Simatelex Manufactory and PT Karyasindo Samudra Biru Shipyard. Hypothesis testing uses a nonparametric test with the Mann-Whitney test. The samples in this study were employees of the two companies, which numbered 100 and 114 people, respectively. The results of the Mann-Whitney test show that the hypothesis is accepted. This study concluded that there are differences in employee performance on the OPP Line of PT Simatelex Manufactory and PT Karyasindo Samudra Biru Shipyard,